Emily & Jackson hiding out - Naylor, Phyllis Reynolds (Delacorte Press, 2012)
Things start looking up for Emily and Jackson when Emily's inheritance clears and Aunt Hilda becomes her legal guardian and offers to become Jackson's, as well, but Uncle Victor reappears, willing to do anything to steal Emily's fortune.